2018
DOI: 10.1002/chem.201706073
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Red‐Emissive Probe for the Selective Fluorescent Detection of Cysteine by Deprotection/Cyclization Cascade Resulting in Large Stokes’ Shift

Abstract: Cysteine plays a crucial role in cellular functions and in human pathologies. However, the development of cysteine probes with extremely accurate detection is still a key challenge for the field. Herein, we have fully characterized and developed a novel selective fluorescent probe: red emission, aqueous detection and large Stokes' shift for cysteine (Reals-C). Key in the probe synthesis is a Michael addition onto an acroylate group and subsequent intramolecular cyclization. The probe exhibits analyte detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Increased reactivity towards Cys was observed along with increasing pH values for both probes. These observations correlated well with previous reports describing the larger concentration of thiolate species in higher pH environments . Lysosomes are spherical‐shaped, catabolic organelles with an acidic interior (pH 4.0–6.0) .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Increased reactivity towards Cys was observed along with increasing pH values for both probes. These observations correlated well with previous reports describing the larger concentration of thiolate species in higher pH environments . Lysosomes are spherical‐shaped, catabolic organelles with an acidic interior (pH 4.0–6.0) .…”
Section: Resultssupporting
confidence: 92%
“…These observations correlatedw ell with previous reports describing the larger concentration of thiolates peciesi nh igher pH environments. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Lysosomes are spherical-shaped, catabolic organelles with an acidic interior (pH 4.0-6.0). [63] Although diminished reactivity towards Cys was found, both Lyso-S and Lyso-D could functionp roperly under al ysosomal pH environment.…”
Section: Effect Of Phmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group has synthesized a series of molecular probes bearing organic chalcogenide sites (i.e., S, Se, and Te) [18][19][20][21]. These chalcogenide probes can indicate the presence and concentration of important analytes, such as reactive oxygen species (ROS) and reactive nitrogen species (RNS), including hydrogen peroxide (…”
Section: Figure 1 Illustration Of the Function And Interrelationshipmentioning
confidence: 99%
“…Additionally, the ratiometric fluorescent probes could provide an inherent reliability originating from its effective self-calibration advantage by monitoring two well-resolved emissions (Kikuchi et al, 2004; Demchenko, 2010; Lee et al, 2015). Although a number of fluorescent probes for Cys detection and imaging have been reported, most of them could not discriminate Cys from Hcy/GSH due to their similar molecular structures and reactivity (Chen et al, 2017, 2018; Li et al, 2017; Liu X. et al, 2017; Nawimanage et al, 2017; Wang F. et al, 2017; Wang Q. et al, 2017, 2018a; Wu et al, 2017; Yin et al, 2017; Yue et al, 2017a,b; Zhang et al, 2017, 2018a,b; Hou et al, 2018; Kim et al, 2018; Ren et al, 2018; Song et al, 2018; Tian et al, 2018; Wang et al, 2018b; Wang J. et al, 2018; Wang L. et al, 2018; Sheng et al, 2019). Several ratiometric fluorescent probes for Cys have been developed (Lv et al, 2014; Feng et al, 2017; Liu G. et al, 2017; Wang F. et al, 2017; Wang L. et al, 2018 Wu et al, 2018; Yue et al, 2018; Zhu et al, 2018), but only a few of them showed the fluorescence emission in NIR region (Feng et al, 2017; Zhu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%